Therapeutic effect of low-dose BMSCs-Loaded 3D microscaffold on early osteonecrosis of the femoral head - Minzheng Guo; Baochuang Qi; Zijie Pei; Haonan Ni; Junxiao Ren; Huan Luo; Hongxin Shi; Chen Meng; Yang Yu; Zhifang Tang; Yongqing Xu; Qingyun Xue; et al. (Materials Today Bio)
The early treatment of Osteonecrosis of Femoral Head (ONFH) remains a clinical challenge. Conventional Bone Marrow Mesenchymal Stem Cell (BMSC) injection methods often result in unsatisfactory outcomes due to mechanical cell damage, low cell survival and retention rates, inadequate cell matrix accumulation, and poor intercellular interaction. In this study, we employed a novel cell carrier material termed ''3D Microscaffold'' to deliver BMSCs, addressing these issues and enhancing the therapeutic effects of cell therapy for ONFH. We injected 3D microscaffold loaded with low-dose BMSCs or free high-dose BMSCs into the femoral heads of ONFH rats and assessed therapeutic effects using imaging, serology, histology, and immunohistochemistry. To understand the mechanism of efficacy, we established a co-culture model of human osteoblasts and BMSCs, followed by cell proliferation and activity detection, flow cytometry analysis, Quantitative RT-PCR, and Western blotting. Additionally, RNA sequencing was performed on femoral head tissues. Results showed that the 3D microscaffold with low-dose BMSCs had a therapeutic effect comparable to high-dose free BMSCs. Osteoblasts in the 3D microscaffold group exhibited superior phenotypes compared to the non-3D microscaffold group. Furthermore, we have, for the first time, preliminarily validated that the low-dose BMSCs-loaded 3D microscaffolds may promote the repair of femoral head necrosis through the synergistic action of the MAPK and Hippo signaling pathways.